2005
DOI: 10.1002/polb.20509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pyridazine structure on thin‐film polymerization and phase behavior of thermotropic liquid crystalline copolyesters

Abstract: An intensive study has been conducted to compare the effects of malei hydrazine (MH) and hydroquinone (HQ) on the liquid crystallinity and phase transition behavior in the ABA/HQ/TFTA and ABA/MH/TFTA copolyesters (p‐acetoxybenzoic acid (ABA) and tetrafluoroterephthalic acid (TFTA)). These two copolyesters were prepared by thin‐film polymerization and characterized by differential scanning calorimetry (DSC), polarizing light microscope (PLM), wide‐angle X‐ray diffraction (WAXD), as well as Cerius2 computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The effect of pyridazine structure on phase behaviour of thermotropic liquid crystalline copolyesters has been studied by Teoh et al (Scheme 35). 75 Authors have carried out the effects of maleic hydrazine (MH) and hydroquinone (HQ) on the liquid crystallinity and phase transition behaviour in the ABA/HQ/ TFTA 168 and ABA/MH/TFTA 167 copolyesters (p-acetoxybenzoic acid (ABA) and tetrafluoroterephthalic acid (TFTA)) prepared by thin film polymerization. It has been demonstrated that the system 167 is energetically more favourable to mesophase formation than the system 168.…”
Section: Liquid Crystalsmentioning
confidence: 99%
“…The effect of pyridazine structure on phase behaviour of thermotropic liquid crystalline copolyesters has been studied by Teoh et al (Scheme 35). 75 Authors have carried out the effects of maleic hydrazine (MH) and hydroquinone (HQ) on the liquid crystallinity and phase transition behaviour in the ABA/HQ/ TFTA 168 and ABA/MH/TFTA 167 copolyesters (p-acetoxybenzoic acid (ABA) and tetrafluoroterephthalic acid (TFTA)) prepared by thin film polymerization. It has been demonstrated that the system 167 is energetically more favourable to mesophase formation than the system 168.…”
Section: Liquid Crystalsmentioning
confidence: 99%
“…To date, four experimental methods have been developed to investigate the molecular director around disclination of LCPs: surface microcracks decoration, band-texture decoration, lamellar decoration, and focal−conic texture decoration. , The surface microcrack, band-texture decoration, and lamellar decorations were reviewed by Qian et al in 1995, while focal−conic texture decoration was discovered only in 2000.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the fact that pyridazine rings change the planarity of the polymer structure, which will then strongly disturb the chain packing, compared with the linear, aliphatic butane diol chain extender. Therefore, pyridazine heterocyclic ring interrupts the chain orientation and eventually inhibits the regular chain packing of the crystallization process 19. In general, DHPyd based‐PUs exhibit good mechanical properties due to the cumulative effect of the formation quite a few of hydrogen bonds and the stiffness provided by the heterocyclic rings.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, pyridazine heterocyclic ring interrupts the chain orientation and eventually inhibits the regular chain packing of the crystallization process. 19 In general, DHPyd based-PUs exhibit good mechanical properties due to the cumulative effect of the formation quite a few of hydrogen bonds and the stiffness provided by the heterocyclic rings.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation